Loess-Palaeosol Sequences in the Kashmir Valley, NW Himalayas: A Review - Dar, Reyaz A.; Zeeden, Christian (Frontiers in Earth Science, 2020)
Loess deposits and intercalated palaeosols are widespread in the Quaternary record, and these have been extensively used to gain insights into continental paleoclimatic and paleo-environmental conditions and changes. Especially over Eurasia, loess geoarchives play an important role for our understanding of past changes. Loess covers almost 500 km2 of the Kashmir Valley in north-western India, it occurs dominantly plateau positions, but also on terraces and sometimes form slope deposits with thicknesses ranging from several to more than 20meters. For the time being, however, the timing of the initiation of the loess accumulation, the provenance, the grain size composition and also the paleo-environment have not been studied systematically and yet only little quantitative data is available. Yet it is clear that deposition rates are at least comparable to European loess, and that the presence of multiple palaeosols intercalated in the loess can provide valuable information on the history of the region. The limited available data hinders regional and continental correlation, and tapping its value as archive of past environmental changes in this sensitive region with influence from Westerlies and the Indian Monsoon. However, several characteristic palaeosol patterns can be traced throughout the Kashmir valley, which provide stratigraphic information. Several studies investigate physical and chemical properties of the loess-paleosol sequences and conclude to its aeolian origin and recorder of past climates. The intensity of soil formation phases is traced through various proxies in low resolution and yet without conclusive age control. Here we review the exiting literature, available data, and interpretations from loess-palaeosol sequences in the Kashmir Valley. These are placed in the context of our own observations and loess from the Indian subcontinent.